Potential of elateriospermum tapos blume in ameliorating maternal metabolic syndrome on female offspring of sprague dawley rats through the hypothalamic feeding circuitry - Balan, Santhra Segaran (2022)
Maternal obesity is often related to balancing daily lifestyle intake of high-fat diet or western diet. This will affect endogenously on altering the daily activity of metabolism and lead to childhood obesity. The central nervous system (CNS) plays a vital role in regulating food intake and energy usage to maintain the energy balance in the body. Specifically, the hypothalamus monitors and response to the peripheral signal such as Neuropeptide Y (NPY), proopiomelanocortin (POMC) and leptin receptor (Obr), which involve feeding circuitry organisms. Elateriospermum tapos (E.tapos) known as buah perah locally and contain flavonoid in seed and shell which help reduce body weight. This study investigates the effect of E. tapos supplementation on female offspring through hypothalamic feeding circuitry. Thirty adult female Sprague Dawley rats were divided into two groups. Six rats assigned as a control group (DCG) were fed with standard chow, and 24 rats were assigned to an obese group with a high-fat diet (HFD) and cafeteria food to generate obesity for five weeks. HFD rats were later assigned as negative group (DNG), positive group (DPG) with 200mg/kg of orlistat drug, treatment 1 (DTX1) with 200 mg/kg E.tapos seed, and treatment 2 (DTX2) with 200 mg/kg E.tapos shell daily for six weeks. Female rats were mated and culled at postnatal day 21 (PND21). Organs, blood, and brain were collected for analysis. Dams from the DTX2 group slightly reduced body weight and retroperitoneal whited adipose tissue (RpWAT) compared to the DNG group. Their offspring from treatment 2 (OTX2) offspring; show the same effect at mother dams. Total cholesterol levels among DTX2 and OTX2 show a significant decrease (p<0.05) in dams and offspring. The atherosclerotic lesion was present in group DTX1, DTX2, offspring from treatment 1 (OTX1), and OTX2 compared to DNG and offspring from negative (ONG) group rats. Liver profile on alanine transaminase and aspartate transaminase level show significant changes (p<0.05) among all dams and offspring. Histopathological grading of the liver section of DNG, ONG, and offspring from positive (OPG) displayed the presence of ballooning hepatocytes. Histology of RpWAT of DTX1, DTX2, OTX1, and OTX2 showed normal adipocytes with a similar pattern of DCG and offspring from the control (OCG) group. Plasma leptin shows significant changes (p<0.05) among DTX2 and OTX2 compared to DNG and ONG groups. Expression of protein OBR, POMC, and NPY was analyzed using a western blot. Results show that the expression in DNG and ONG from this protein is more prominent than in other groups. In conclusion, the E.tapos shell had a more significant effect on ameliorating maternal obesity on female offspring at PND21 than the E.tapos seed.